Bulk Spin-Wave Filtration at the Interface of Two Uniaxial Ferromagnetic Media - Yu.I. Gorobets; S.O. Reshetnyak (Журнал нано- та електронної фізики)
In this paper the dependencies are obtained of spin wave reflection coefficients on frequency and external magnetic field for ferromagnetic structure in the exchange mode, when the influence of magnetostatic part of energy is neglected as compared with exchange one. It is shown that ferrogarnet structure, having very small damping parameter, is good for high-quality filtration of spin waves because it gives large change of reflection coefficient in small intervals of frequencies and external magnetic fields.